Learning Loss Lessons in Moji-Goi - Sri Aju - Indrowaty; Eti Setiawati; Wiranto Aji Dewandono; Nurul Faizah; Sofyan Sukrian Sachputra; Sony Difa Febrianda (EDUCATIO : Journal of Education, 2024)
After the COVID-19 pandemic for approximately 2 years, a lot of learning that is usually face-to-face is finally done online or in hybrid ways. Certain learning phases, like writing hiragana, katakana, and kanji in a face-to-face classroom, are not transferable to online learning. The goal of this study is to mitigate the learning loss that happens when face-to-face instruction in Japanese language classes is substituted by online learning. The method used is descriptive qualitative by presenting various ways of teaching Moji-Goi using learning media and YouTube. According to John Keller (2021), learning should use the ARCS method (Attention, Relevance, Confidence, and Satisfaction) so that learning loss can be overcome with various treatments including the ARCS method and various uses of media such as cards, games, songs, role-play, and YouTube. This research also intends to introduce JF (Japan Foundation) Standard learning and share information about Japanese language teaching, especially about Moji-Goi (Vocabulary-letters)